Brittle-Cornea-Syndrom Typ 1 durch Compound-Heterozygotie zweier Mutationen im ZNF469-Gen - Menzel-Severing, Johannes; Meiller, Ralph; Kraus, Cornelia; Trollmann, Regina; Atalay, Deniz (Ophthalmologe, 2019)
We report the case of a 3-year-old boy presenting with bilateral keratoglobus and blue sclera in addition to hallux valgus, arachnodactyly, small joint hypermobility, mitral valve dysfunction and a history of generalized muscular hypotonia in early infancy. Molecular genetics provided evidence of two pathogenic mutations in the ZNF469 gene (compound heterozygosity) leading to the diagnosis of brittle cornea syndrome type 1. In addition to neuropediatric care, spectacles were prescribed to correct refractive error and for ocular protection. Owing to the thin cornea and sclera, eye injuries are the main cause for irreversible visual loss in this disease.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Blue sclera; Connective tissue disease; Hereditary eye disease; Keratoglobus; Pediatric ophthalmology